Establishing and managing a periodontal biobank for research: The sharing of experience - Vaithilingam R.D.; Safii S.H.; Baharuddin N.A.; Karen-Ng L.P.; Saub R.; Ariffin F.; Ramli H.; Sharifuddin A.; Hidayat M.F.H.; Raman R.; Chan Y.K.; Rani N.A.; et al. (Blackwell Publishing Ltd, 2024)
Indexed by WOS/Scopus